As ações extensionistas do Instituto Federal Farroupilha como dispositivos para o desenvolvimento regional - Aguiar, Mariane Rodrigues Volz de (2019)
The Federal Institutes are framed as a educational public policies committed to the transformation and diffusion of knowledge, capable of changing social life and establish a more direct interaction between the public sector and society. However, consolidating itself as a reference in teaching, research and extension, focusing on vocational, scientific and technological training at all levels, besides being a collective space that allows the exchange of experiences and interactions with the community, that make the purposes of these institutions challenging. In this sense, the extension presents itself as a key strategy for the Federal Institutes, with the objective of integrating and articulating the institution, social actors and community in search of socioeconomic and cultural development within the region of action and scope. Therefore, this study proposal sought to analyze how the extension activities of the Farroupilha Federal Institute (IFFAR) have been contributing to regional development, based on the demands presented by the Regional Development Council (COREDE) of Vale do Jaguari. For that, a research of qualitative character was carried out, using as method the bibliographical and documentary research, apply on Institutional Development Plan (PDI) and Strategy Development Plan (PED) of Vale do Jaguari COREDE; also analyzed the minutes of Vale do Jaguari COREDE’s meetings and the IFFAR extension projects , in the Jaguari and São Vicente do Sul campus, in order to identify how the social demands were exposed by this council, and how they were received by the IFFAR. The results of this study indicated that there are gaps in relation to the level of interaction between IFFAR and Vale do Jaguari COREDE. It was verified the need to improve the extension projects executed by the Jaguari and São Vicente do Sul campus, in order to identify the demand source and relate it to institutional strategies indicated in the IFFAR PDI and in the PED of the Vale do Jaguari COREDE. Likewise, it has been identified that there is a lack of understanding of social actors, these occupants of representation seats in the Vale do Jaguari COREDE, in relation to their social representation role and the importance of the effective performance of the representatives of the educational institutions in COREDE for the alignment of institutional strategies and the promotion of regional development. From these results, series of actions are proposed to the institutions aimed at the institutional interaction and identification of social demands; the enhancement of extension projects; and an awareness of the role of social representation